Resolving when (and where) the Thylacine went extinct - Brook, Barry W.; Sleightholme, Stephen R.; Campbell, Cameron R.; Jarić, Ivan; Buettel, Jessie C. (The Science of the total environment, 2023)
Like the Dodo and Passenger Pigeon before it, the predatory marsupial Thylacine (Thylacinus cynocephalus), or ‘Tasmanian tiger’, has become an iconic symbol of anthropogenic extinction. The last captive animal died in 1936, but even today reports of the Thylacine's possible ongoing survival in remote regions of Tasmania are newsworthy and capture the public's imagination. Extirpated from mainland Australia in the mid-Holocene, the island of Tasmania became the species' final stronghold. Following European settlement in the 1800s, the Thylacine was relentlessly persecuted and pushed to the margins of its range, although many sightings were reported thereafter—even well beyond the 1930s. To gain a new depth of insight into the extinction of the Thylacine, we assembled an exhaustive database of 1237 observational records from Tasmania (from 1910 onwards), quantified their uncertainty, and charted the patterns these revealed. We also developed a new method to visualize the species' 20th-century spatio-temporal dynamics, to map potential post-bounty refugia and pinpoint the most-likely location of the final persisting subpopulation. A direct reading of the high-quality records (confirmed kills and captures, in combination with sightings by past Thylacine hunters and trappers, wildlife professionals and experienced bushmen) implies a most-likely extinction date within four decades following the last capture (i.e., 1940s to 1970s). However, uncertainty modelling of the entire sighting record, where each observation is assigned a probability and the whole dataset is then subject to a sensitivity analysis, suggests that extinction might have been as recent as the late 1980s to early 2000s, with a small chance of persistence in the remote south-western wilderness areas. Beyond the intrinsically fascinating problem of reconstructing the final fate of the Thylacine, the new spatio-temporal mapping of extirpation developed herein would also be useful for conservation prioritization and search efforts for other rare taxa of uncertain status. [Display omitted] •The Thylacine (Tasmanian Tiger) was famously thought to have gone extinct in 1936.•We compiled an exhaustive record of later possible sightings to test this assertion.•Using uncertainty modelling, we mapped the likely regional extirpation pattern.•Contrary to the consensus, this iconic predator probably persisted until the 1980s.•Our new spatial method will be useful for inferring any species' range contraction.